Pectinase production from banana peel biomass via the optimization of the solid-state fermentation conditions of Aspergillus niger strain - Rasit, Nazaitulshila; Yong, Sin Sze; Hassan, Mohd Ali; Ooi, Chee Kuan; Hamzah, Sofiah; Wan Abdullah, Wan Rafizah; Siddique, Md. Nurul Islam (Universiti Putra Malaysia Press, 2022)
In this study, the biomass of banana peel was used to produce pectinase via optimization of solid-state fermentation conditions of the filamentous fungi Aspergillus niger (A. niger). The operating conditions of solid-state fermentation were optimized using the method of full factorial design with incubation temperature ranging between 25 °C and 35 °C, moisture content between 40% and 60%, and inoculum size between 1.6 x 106 spores/ mL and 1.4 x 107 spores/mL. Optimizing the solid-state fermentation conditions appeared crucial to minimize the sample used in this experimental design and determine the significant correlation between the operating conditions. A relatively high maximal pectinase production of 27 UmL-1 was attained at 35° C of incubation, 60% of moisture content, and 1.6 x 106 spores/mL of inoculum size with a relatively low amount of substrate (5 g). Given that the production of pectinase with other substrates (e.g., pineapple waste, lemon peel, cassava waste, and wheat bran) generally ranges between 3 U/mL and 16 U/mL (Abdullah et al., 2018; Handa et al., 2016; Melnichuk et al., 2020; Thangaratham and Manimegalai, 2014; Salim et al., 2017), thus the yield of pectinase derived from the banana peel in this study (27 U/mL) was considered moderately high. The findings of this study indicated that the biomass of banana peel would be a potential substrate for pectinase production via the solid-state fermentation of A. niger.